On some specifics in the training of foreign language teachers - Koeva, Yanka (Yearbook of the Department of Foreign Languages and Cultures, 2024)
The aim of this paper is to highlight key aspects of the education and training of foreign language teachers. It examines the didactic and methodological preparation required, focusing on the knowledge, skills, and attitudes that must be developed. In line with the CEFR framework, the professional competences of a foreign language teacher include not only the development of linguistic knowledge and communicative skills, but also the fostering of intercultural awareness, the cultivation of independent learning strategies, and the encouragement of personal initiative in pursuing language learning beyond the classroom. Within teacher training, particular emphasis is placed on multilingualism and the intercultural approach. Finally, the paper presents a professional competence model for German language teachers.